The Goodsir brothers from Fife, Scotland: contributions to anatomy, marine zoology and Arctic exploration in the nineteenth century. Issue 1 (April 2020) - Moore, P. G.
Abstract : Three Goodsir brothers, John, Henry ("Harry") and Robert, from Fife, Scotland, all shared an early interest in marine zoology in the early 1800s. They all went on to receive medical training, with the eldest brother, John, eventually becoming Professor of Anatomy in the University of Edinburgh. John's primary claim to biological fame rests on his contributions to cell-doctrine, in which his eminence was on a par with that of Rudolf Virchow. In his youth, however, John (in concert with younger brother Harry) had become interested in marine zoology, and, as students in Edinburgh, they shared rooms with marine zoologist Edward Forbes. Harry Goodsir, however, was much more of a marine naturalist than John. His life was tragically cut short by his perishing, together with the rest of his shipmates on HMS Erebus, on the third Franklin expedition to the Arctic regions, that one being by ship during a quest for the elusive Northwest Passage. A younger brother, Robert, undertook two later Arctic voyages in search of Harry and his doomed shipmates, making natural history observations on sea birds and marine organisms along the way.